Few-femtosecond passage of conical intersections in the benzene cation - Galbraith, M. C. E.; Scheit, Simona; Golubev, Nikolay V.; Despré, Victor; Kuleff, Alexander I.; Köppel, Horst (Nature Communications, 2017)
Attosecond science is beginning to provide the tools to study the previously unattainable crucial first few femtoseconds of photochemical reactions. Here, the authors investigate extremely rapid population transfer via conical intersections in the excited benzene cation, both by experiment and computation.
Gesehen am 12.06.2018